2012
DOI: 10.1016/j.jpsychores.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and mood disorders in U.S. adolescents: Sex-specific associations with symptoms, diagnoses, impairment and health services use

Abstract: Objective To report sex-specific associations between cigarette smoking and DSM-IV disorders, symptoms, and mental health services use related to depression and anxiety in a nationally representative sample of U.S. adolescents. Methods Data on two samples were drawn from the 1999–2004 National Health and Nutrition Examination Surveys to examine the association of ever smoking (versus never smoking) with depression (n=1884 12–15 year-olds) and anxiety (n=6336 12–19 year-olds). Sex-specific associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 84 publications
2
18
0
1
Order By: Relevance
“…Evidence suggests that anxiety is a risk factor for cigarette use [ 33 ] and that regular cigarette smoking is associated with anxiety disorders [ 34 ]. Although several studies have reported no association between anxiety and STU [ 35 , 36 ], in our analysis, we found that higher levels of anxiety were associated with STU at each home assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that anxiety is a risk factor for cigarette use [ 33 ] and that regular cigarette smoking is associated with anxiety disorders [ 34 ]. Although several studies have reported no association between anxiety and STU [ 35 , 36 ], in our analysis, we found that higher levels of anxiety were associated with STU at each home assessment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there have been large-scale epidemiological studies on adolescents that have reported that smoking may influence depression (Park et al, 2010;Patton et al, 1998;Wu & Anthony, 1999). According to a cross-sectional study by Richardson et al (Richardson et al, 2012) conducted on 1,884 adolescents aged 12-15 who participated in the U.S. National Health and Nutrition Survey performed from 1999 through 2004, after the control of socio-demographic factors, smokers were 2.8 times more likely to suffer from depression than non-smokers. In addition, in a study on 1,709 adolescents aged 14-18, smokers were 1.9 times more likely to suffer from major depressions than non-smokers (Brown et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…According to such studies, smokers have a 1.9-2.8 times greater risk of depression than nonsmokers (Brown et al, 1996;Richardson et al, 2012). On the other hand, other studies have reported that smoking is not related with depression or anxiety (Takemura et al, 1999;Williams & Adams-Campbell, 2000).…”
Section: Reviewing Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…There is comorbidity between depression and smoking (Conway et al, 2017;Polednak, 2014;Weinberger et al, 2016). Richardson, He, Curry, and Merikangas (2012) 2013 for those who experienced depression and were current smokers. These studies suggest a co-segregation of the two syndromes.…”
Section: The Relationship Between Smoking and Depression In Adolescentsmentioning
confidence: 99%